1994
DOI: 10.1088/0029-5515/34/3/i12
|View full text |Cite
|
Sign up to set email alerts
|

Experimental determination of non-diffusive toroidal momentum flux in JT-60U

Abstract: Toroidal momentum transport is examined experimentally by using on-and off-axis tangential neutral beam injections on the JT-60U tokamak. From a steady state momentum balance analysison the assumption that momentum flux is diffusiveit is found that the profiles of the momentum diffusivity are quite different in the two cases of on-and off-axis beam injections. In addition, transient toroidal momentum transport was examined by using a momentum source modulation experiment. On the assumption that the toroidal mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
81
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(81 citation statements)
references
References 8 publications
0
81
0
Order By: Relevance
“…Modulation at a suitable frequency has the advantage of optimizing the S/N ratio by averaging over several cycles and has been used successfully to study electron and more recently ion heat transport, and also particle and impurity transport (see [18] for a recent review). Its application to momentum transport studies using Neutral Beam Injection (NBI) modulation is a recent development, with a couple of studies reported in JT-60U [19,20], one experiment reported in JET [21,22,23] and one in DIII-D [24]. The use of magnetic perturbations to brake the plasma was reported in DIII-D [25] and NSTX [24,26,27] as another means to induce a transient from which it is possible to infer diffusivity and convection separately.…”
Section: Introductionmentioning
confidence: 99%
“…Modulation at a suitable frequency has the advantage of optimizing the S/N ratio by averaging over several cycles and has been used successfully to study electron and more recently ion heat transport, and also particle and impurity transport (see [18] for a recent review). Its application to momentum transport studies using Neutral Beam Injection (NBI) modulation is a recent development, with a couple of studies reported in JT-60U [19,20], one experiment reported in JET [21,22,23] and one in DIII-D [24]. The use of magnetic perturbations to brake the plasma was reported in DIII-D [25] and NSTX [24,26,27] as another means to induce a transient from which it is possible to infer diffusivity and convection separately.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, spontaneous toroidal flow becomes important in the next fusion devices such as ITER, where the toroidal flow velocity driven by external momentum is expected to be insufficient to stabilize the MHD mode. The mechanism of driving the spontaneous toroidal flow is interesting from the viewpoint of momentum transport physics and has been investigated in tokamaks, both experimentally and theoretically [2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The toroidal flow has been considered to be determined by the radial transport of momentum driven by neutral beam injection (NBI) with anomalous shear viscosity [8,9]. Although the E 3 B velocity shear due to the toroidal flow can be important in the plasma core [10], there have been few experiments that demonstrate a spontaneous toroidal flow not driven by NBI in tokamaks [11][12][13][14]. It is generally the case in tokamaks that the plasma rotates parallel (antiparallel) to the plasma current for the coinjected (counterinjected) NBI, which corresponds to a positive (negative) radial electric field ͑E r ͒ in L-mode plasmas [15].…”
mentioning
confidence: 99%